Cultivating microalgae in wastewater for biomass production, pollutant removal, and atmospheric carbon mitigation; a review - Shahid, Ayesha; Malik, Sana; Zhu, Hui; Xu, Jianren; Nawaz, Muhammad Zohaib; Nawaz, Shahid; Asraful Alam, Md; Mehmood, Muhammad Aamer (The Science of the total environment, 2020)
[Display omitted] •Microalgae are the most promising photoautotrophs to fix atmospheric carbon.•Requirement of huge amounts of freshwater to culture microalgae is challenging.•Alternatively, wastewater cultivation offers low-cost biomass production.•Wastewater nutrient stress can manipulate the microalgal metabolite content.•Mixed cultivation offers additional benefits of efficient wastewater treatment. Water shortage is one of the leading global problems along with the depletion of energy resources and environmental deterioration. Recent industrialization, global mobility, and increasing population have adversely affected the freshwater resources. The wastewater sources are categorized as domestic, agricultural and industrial effluents and their disposal into water bodies poses a harmful impact on human and animal health due to the presence of higher amounts of nitrogen, phosphorus, sulfur, heavy metals and other organic/inorganic pollutants. Several conventional treatment methods have been employed, but none of those can be termed as a universal method due to their high cost, less efficiency, and non-environment friendly nature. Alternatively, wastewater treatment using microalgae (phycoremediation) offers several advantages over chemical-based treatment methods. Microalgae cultivation using wastewater offers the highest atmospheric carbon fixation rate (1.83 kg CO2/kg of biomass) and fastest biomass productivity (40–50% higher than terrestrial crops) among all terrestrial bio-remediators with concomitant pollutant removal (80–100%). Moreover, the algal biomass may contain high-value metabolites including omega-3-fatty acids, pigments, amino acids, and high sugar content. Hence, after extraction of high-value compounds, residual biomass can be either directly converted to energy through thermochemical transformation or can be used to produce biofuels through biological fermentation or transesterification. This review highlights the recent advances in microalgal biotechnology to establish a biorefinery approach to treat wastewater. The articulation of wastewater treatment facilities with microalgal biorefinery, the use of microalgal consortia, the possible merits, and demerits of phycoremediation are also discussed. The impact of wastewater-derived nutrient stress and its exploitation to modify the algal metabolite content in view of future concerns of cost-benefit ratios of algal biorefineries is also highlighted.